Interakcije v mešanicah polimerov na osnovi poliesteruretanov - Ulčnik-Krump, Manica (Kovine zlitine tehnologije, 1995)
Synthesised thermoplastic polyurethane (TPU) and chlorinated thermoplastic polyurethane (CTPU) were blended with 25 wt.% of styrene/acrylonitriles with different amount of acrylonitrile (SAN34, SAN24). The samples were prepared insolution of dimethylformamide (DMF). The interactions between polymers, the effect of amount of acrylonitrile in SAN and the structure of polyuretane in TPU/SAN and CTPU/SAN blends were studied by differential scanning calorimetry (DSC).
Keywords: polimeri; poliuretani; interakcije; termične lastnosti